Implementasi TPACK dalam Pembelajaran PAI dan Tantangan Guru pada Abad 21 di SD Muhammadiyah Bodon Kotagede - Aulia Wulan; Lovandri Dwanda Putra; Syifa' Inda Robbi; Dinnia Hafiza Ilmi; Wahyu Anisa Fatikhah (Penerbit Widina, Widina Media Utama, 2026)
Twenty-first-century education demands innovative technological integration; however, Islamic Education (PAI) teachers often encounter specific challenges in aligning digital tools with religious values at the elementary school level. This study aims to provide an empirical overview of how PAI teachers implement the Technological Pedagogical Content Knowledge (TPACK) framework and to identify the challenges faced during this process at SD Muhammadiyah Bodon Kotagede. Employing a descriptive qualitative approach, data were collected through participant observation, in-depth interviews, and documentation of teaching instruments from purposively selected PAI teachers. The results indicate that TPACK implementation has been adequately internalized through the use of Power Point media for visualizing Tajwid material, combined with direct practice using the Al-Qur'an Mushaf. Despite facing technical constraints such as internet stability and student dependence on visual displays, the school has successfully mitigated these obstacles through infrastructural support and routine technology training for educators. This study concludes that the success of TPACK in PAI learning depends not only on technological sophistication but also on the teacher's ability to maintain the